UJI COBA PENANAMAN MANGROVE DI BEKAS TAMBAK BUDIDAYA UDANG DI KABUPATEN PEMALANG - Sri Puryono KS. (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2006)
The acceleration of mangrove deforestationhas become an issue ofgreat concernfor several yecirs in the world. Factors responsible for the depletion of the mangroveforest included mangrove clearing for human settlement, commercial shrimp and prawn hatcheries, salt production. industry,recreationarea, and an harbor arefor mangrove environ/menbetterment. Theplantation trial for reboisation was started at Pemalang District. Therewere technical problems in this activity such as: low level and, high salinity, unsmokly streamflow eel. Based on the view of